Comparison of Intracoronary Tirofiban And Intravenous Tirofiban for Major Adverse Cardiac Events and Cerebrovascular Accident : Comparison of Intracoronary Tirofiban and Intravenous Tirofiban - Bukhari, Syed Husnain Raza; Rana, Muhammad Anjum; Mirza, Muhammad Shahjehan; Kazmi, Muhammad Nouman; Ur Rehman, Zia; Sulah Ud Din, Junaid (Pakistan Journal of Health Sciences, 2023)
Major Adverse Cardiovascular Events (MACE) and and Cerebrovascular Accidents (CVA) have become primary areas of interest due to the ongoing focal research in cardiovascular diseases. Objective: To assess the frequency of major adverse cardiac events and cerebrovascular accident<span class="NormalTextRun SCXW201833491 BCX8" data-ccp-charstyle="Other_" data-ccp-charstyle-defn=""ObjectId":"566c83ec-64d4-462d-8fd8-d33109af2a47|102","ClassId":1073872969,"Properties":[469775450,"Other_",201340122,"1",134234082,"true",134233614,"true",469778129,"Other",335572020,"1",134231262,"true",469777841,"Times New Roman",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman",335551547,"1033",469777929,"Other",469778324,"Default Paragraph Font"]" data-ccp-charstyle-linked-defn=""ObjectId":"566c83ec-64d4-462d-8fd8-d33109af2a47|103","ClassId":1073872969,"Properties":[469775450,"Other",201340122,"2",134234082,"true",134233614,"true",469778129,"Other0",335572020,"1",469777841,"Times New Roman",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman",268442635,"22",335551547,"1033",335559740,"480",201341983,"0",335559739,"260",134245417,"false",469777929,"Other_",469778324,"Normal"]">s for intracoronary tirofiban and intravenous tirofiban. Methods: It was a comparative study conducted at the Punjab Institute of Cardiology, Lahore from March 2019 to March 2020. A total of 250 patients of both genders, aged between 20 to 65 years were enrolled in this study who had STEMI and have high thrombus burden or TIMI flow grade < 3 during primary PCI. They were divided into two groups namely intracoronary tirofiban group and intravenous tirofiban. The impact of intracoronary tirofiban versus intravenous tirofiban outcomes were assessed. Results: Statistically insignificant difference in MACE (myocardial infarction, cerebrovascular accident & revascularization) between intracoronary & intravenous tirofiban groups was noted. The frequency distribution for cerebrovascular accidents (CVA) showed that haemorrhage was found similar in both groups. Ischemic stroke, in patients of the intracoronary tirofiban group compared with intravenous tirofiban group, was 1 (0.8%) vs 3 (2.4%) with p-value 0.348 respectively. Reversible ischemic neurological deficit (RIND) was found in 3 (2.4%) in the intracoronary and 4 (3.2%) in the intravenous group. Transient ischemic attack (TIA) found in the intracoronary was 8(6.4%) whereas in the intravenous group was 9 (7.2%). Conclusions: The results of our study make us conclude that tirofiban when given intracoronary or intravenous does not show any significant difference for major adverse cardiac events and cerebrovascular accidents.